Pressure Fluctuation and Flow Characteristics in a Two-Stage Double-Suction Centrifugal Pump - Zhicong Wei (Symmetry, 2019)
Pressure fluctuation is the primary factor that affects the stability of turbomachines. The goal of the present work is to explore the propagation of pressure fluctuations in a two-stage double-suction centrifugal pump. The pressure fluctuation characteristics of each component of a two-stage double-suction centrifugal pump are simulated under four typical flow rates based on the SST k-ω turbulence model. It is shown that the pressure fluctuation frequency at blade passing frequency and its first harmonic is the same at the suction chamber, the leading edge, and the middle of the first-stage impeller, which is different from the rotor–stator interaction. Moreover, the uneven impeller inlet flow distribution will produce fluctuations with rotation frequency and its harmonics at the leading edge of the impellers in both stages. Finally, broadband frequency is found at the trailing edge of the impellers in both stages associated with the first harmonic of the rotation frequency, especially under the part load condition. The large size backflow vortex appears in the blade flow channel leading to the low-pressure zone between the impeller, the tongue, and the start of the partition. That is why the pressure drops significantly twice in one rotation period when the blades pass through the tongue and the start of the partition.